Pengaruh Manajemen Sarana dan Prasarana terhadap Kegiatan Belajar Mengajar di TK Al-Fadlillah Maguwoharjo Yogyakarta - Hasanah, Raudatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
This study aims to determine the effect of facilities and infrastructure management on teaching and learning activities at the kindergarten Al-Fadlillah Maguwoharjo Yogyakarta. This research uses a quantitative approach eith a correlational analysis method. Data analysis was performed with a simple linear regression test to determine the effect between facilities and infrastructure management variables (X) and the variables of teaching and learning activities (Y). The results showed a significance value 0,001 smaller than 0,05, which means that there is a significant influence between the management of facilities and infrastructure with teaching and learning activities at the kindergarten Al-Fadlillah Maguwoharjo Yogyakarta. The coefficient value between the two variables is 0,863 or 83,6%. These results, indicate the management of facilities and infrastructure have a positive and significant influence on teching and learning activities by 83,6%. While 16,4% is influenced by other factors, such as the child’s basic abilities, physical and psychological condition of the child, and childrens learning motivation. So, the implementation of structured and controlllled facilities and infrastructure management will support quality improvement in the process of teaching and learning activities at the kindergarten Al-Fadlillah Maguwoharjo Yogyakarta.